DIGITAL MARKETING STRATEGI PROMOSI BERBASIS WEB MOBILE PADA HASIL KERAJINAN TANAH LIAT - Marliyanti Marliyanti; Fista Anisa Zahra (Jurnal Signaling, 2023)
The gem tile industry is an industry in Sidoharjo Village, Pringsewu District which operates in the field of clay tiles, and the type of tile produced is mantili tiles from plain roof tiles. However, based on the results of observations that have been made, it is known that the sales system still uses a conventional system, starting from the ordering process and the payment process. The methodology used in this research is to use the waterfall model because by using this method the company can have a clear and measurable system workflow. From this research, the results obtained are the implementation of a website-based roof tile sales information system which was created to make it easier for owners to promote and market products effectively and efficiently, making it easier for customers to find out information quickly and accurately, just by looking at the website, and making it easier to make payments. . Based on the results of the study and discussion of the design of a website-based gem tile sales application that was created to assist in promotion, marketing and introduce new consumers to products in the gem tile industry, and the system is designed to make it easier for users to access data and information quickly, accurately and effectively. and efficient.